Antibacterial Effect of Nitric Oxide on the Causative Agents of Hospital-Acquired Pneumonia (Experimental Study) - T. P. Kalashnikova; Iu. A. Arsenyeva; N. O. Kamenshchikov; Yu. K. Podoksenov; I. V. Kravchenko; M. V. Chubik; M. R. Karpova; A. E. Myshova; S. A. Bykonia; S. S. Rakitin; M. S. Kozulin; B. N. Kozlov; et al. (Общая реаниматология, 2024)
The aim of the study was to evaluate the antimicrobial effect of single and repeated nitric oxide (NO) exposure on the major pathogens of nosocomial pneumonia isolated from the sputum of cardiac surgery patients.Materials and Methods. A 24-hour culture of microorganisms from pan-resistant isolates of Pseudomonas aeruginosa, Escherichia coli, Acinetobacter baumannii, and Klebsiella pneumoniae from the sputum of inpatient cardiac surgery patients with nosocomial pneumonia, as well as strains of P. aeruginosa and E. coli from the American Type Culture Collection (ATCC), were exposed to 200 ppm NO (experimental sample) or medical air (control sample) in a sealed chamber for 30 minutes. After a single or 4 repeated gas exposure at 4 h intervals, Petri dishes were placed in a thermostat at 37°C and the results were evaluated at 24 and 48 h or at 12, 24, 36 and 48 h, respectively. Grown colonies were counted using an automated colony counter and recorded as CFU/mL.Results. No growth of clinical isolates of P. aeruginosa and E. coli was observed 24 and 48 h after a single exposure to NO. Growth of A. baumannii was lower compared to controls at 24 h but continued at 48 h. No effect of a single exposure to 200 ppm NO on other microorganisms was observed. After 4 exposures to NO, the growth of ATCC E. coli was not detected, the growth of other experimental strains was significantly lower compared to the control (P<0.05).Conclusion. Our results provide a rationale for the use of multiple intermittent inhalation of 220 ppm NO for the treatment of patients with hospital-acquired bacterial pneumonia.